Gut–Liver Immune Response and Gut Microbiota Profiling Reveal the Pathogenic Mechanisms of Vibrio harveyi in Pearl Gentian Grouper (Epinephelus lanceolatus♂ × E. fuscoguttatus♀) - Deng, Yiqin; Zhang, Yaqiu; Chen, Haoxiang; Xu, Liwen; Wang, Qian; Feng, Juan (Frontiers in Immunology, 2020)
Vibrio harveyi causes vibriosis in nearly 70% of grouper (Epinephelus sp.), seriously limiting grouper culture. As well as directly inhibiting pathogens, the gut microbiota plays critical roles in immune homeostasis and provides essential health benefits to its host. However, there is still little information about the variations in the immune response to V. harveyi infection and the gut microbiota of grouper. To understand the virulence mechanism of V. harveyi in the pearl gentian grouper, we investigated the variations in the pathological changes, immune responses, and gut bacterial communities of pearl gentian grouper after exposure to differently virulent V. harveyi strains. Obvious histopathological changes were detected in heart, kidney, and liver. In particular, nodules appeared and huge numbers of V. harveyi cells colonized the liver at 12 h postinfection (hpi) with highly virulent V. harveyi. Although no V. harveyi was detected in the gut, the infection simultaneously induced a gut–liver immune response. In particular, the expression of 8 genes associated with cellular immune processes, including genes encoding inflammatory cytokines and receptors, and pattern recognition proteins, was markedly induced by V. harveyi infection, especially with the highly virulent V. harveyi strain. V. harveyi infection also induced significant changes in gut bacterial community, in which Vibrio and Photobacterium increased but Bradyrhizobium, Lactobacillus, Blautia, and Faecalibaculum decreased in the group infected with the highly virulent strain, with accounting for 82.01% dissimilarity. Correspondingly, four bacterial functions related to bacterial pathogenesis were increased by infection with highly virulent V. harveyi, whereas functions involving metabolism and genetic information processing were reduced. These findings indicate that V. harveyi colonizes the liver and induces a gut–liver immune response that substantially disrupts the composition of and interspecies interactions in the bacterial community in fish gut, thereby altering the gut-microbiota-mediated functions and inducing fish death.